2017
DOI: 10.47197/retos.v0i33.56731
|View full text |Cite
|
Sign up to set email alerts
|

O efeito da idade relativa influencia o tempo de participação competitiva de atletas de handebol do sexo masculino com até 13 anos de idade (Relative age effect affects the time of competitive participation in male handball athletes aged up to 13 years)

Abstract: Resumo: A competição é um ambiente de aprendizagem cuja participação é um elemento de formação esportiva. Este estudo visa analisar as influências do efeito da idade relativa, em inglês, relative age effect (RAE), sobre as decisões dos treinadores no tocante à oportunidade de participação de atletas do sexo masculino de até 13 anos numa competição de handebol. Foram coletados 254 tempos de participação de 100 atletas em 22 partidas. Agrupou-se os dados em gA para atletas com idade acima do 3º quartil; gB para … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 23 publications
1
3
0
7
Order By: Relevance
“…Data revealed that sample is predominantly composed of early-birth young people. Evidence partially confirms the study´s first hypothesis and agrees with several other analyses in the literature which show a high representation of players born within the first six months of the years, in basketball (Arrieta et al, 2016;Ibãnéz et al, 2018) and in other sports modalities (Leonardo, Lizana, Krahenbühl & Scaglia, 2018;Huertas et al, 2019;Jackson & Comber 2020).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Data revealed that sample is predominantly composed of early-birth young people. Evidence partially confirms the study´s first hypothesis and agrees with several other analyses in the literature which show a high representation of players born within the first six months of the years, in basketball (Arrieta et al, 2016;Ibãnéz et al, 2018) and in other sports modalities (Leonardo, Lizana, Krahenbühl & Scaglia, 2018;Huertas et al, 2019;Jackson & Comber 2020).…”
Section: Discussionsupporting
confidence: 91%
“…In this context, the RAE has been extensively studied in different types of sports, such as ice hockey (Fumarco, Gibbs, Jarvis & Rossi, 2017), baseball (Katsumata, Omuro, Mitsukawa & Nakata, 2018), handball (Leonardo, Lizana, Krahenbühl & Scaglia, 2018;Wrang, Rossing, Diernaes, Hansan, Dalgaard-Hansen & Karbing, 2018), volleyball (Papadopoulou et al, 2019), soccer (Bezuglov, Nikolaidis, Khaitin, Usmanova, Luibushkina, Repetiuk & Knechtle, 2019;Bidaurrazaga-Letona, Badiola, Granados, Lekue, Amado & Gil;Huertas et al, 2019;Jackson and Comber, 2020), basketball (Ibãnéz, Mazo, Nascimento & García-Rubio 2018;Ribeiro Júnior, Lobão, Oliveira, Vianna & Werneck, 2020), athletics (Brustio, Kearney, Lupo, Ungureanu, Mulasso, Rainoldi & Boccia, 2019;Valero et al, 2020) and padel (Muñoz, González, Quintana-García & Peinado, 2021). The evidence found has revealed physical, maturational, and psychological differences between players born at the beginning of the year and players born at the end of the year.…”
Section: Introductionmentioning
confidence: 99%
“…This seems to highlight the relevance of the players' experience for the team's final classification (González, 2004). Some studies, however, have indicated that both men and women players from Q1 (born in January-March) tend to play more games (Bjørndal et al, 2018) and more time per game (Leonardo et al, 2018) than those born in the subsequent trimesters. No relationship was found between RAE and the player's position or goals scored.…”
Section: Discussionmentioning
confidence: 99%
“…Another study analysed the relationship between the number of games played and the trimester of birth in an international sample of Norwegian players, finding that players born in Q1 (January-March of the senior year) played more games than those born in Q8 (October-December of the junior year) in the women's youth category (Bjørndal et al, 2018). Likewise, a study of Brazilian U13 male players found that those born in Q1 (January-March) played longer than those born in Q4 (October-December) (Leonardo, Lizana, Krahenbuhl, & Scaglia, 2018).…”
Section: Introductionmentioning
confidence: 97%
“…Identificar quais parâmetros sociais e ecológicos (Balish & Côté, 2011) são responsáveis ou ao menos influenciam no rendimento esportivo são informações essenciais para os agentes envolvidos no planejamento do esporte (autoridades, governantes, gestores) motivo pelo qual, pesquisas têm se ocupado de encontrar variáveis, ambientes, tendências, influências e correlações, a exemplo do local de nascimento (Baker & Logan, 2007;Bruner, Macdonald, Pickett & Côté, 2011;Côté, MacDonald, Baker & Abernethy, 2006;Côté, Baker & Abernethy, 2007;Curtis e Birch,1987;Finnegan, Richardson, Littlewood & Mcardlea, 2016;Lidor, Arnon, Maayan, Gershon & Côté, 2014), influência da família (Côté, 1999;Fredricks & Eccles, 2005;Hopwood, Farrow, MacMahon & Baker, 2015;Woolger & Power, 1993;Sanz-Arazuri, Ponce-De-León-Elizondo, Valdemoros-San-Emeterio & Baena-Extremera, 2018), coaching (Salmela & Moraes, 2003), tamanho da comunidade local ou tamanho da população (Fraser-Thomas, Côté & MacDonald, 2010), o efeito relativo da idade (Baker & Logan, 2007;Barnsley, Thompson & Barnsley, 1985;Bruner et al, 2011;Finnegan et al, 2016;Grondin, Deshaies & Nault, 1984;Hancock, Adler & Côté 2013;Lidor et al, 2014;Leonardo, Lizana, Krahenbuhl & Scaglia, 2018), influência do local de desenvolvimento (Turnnidge, Hancock & Côté, 2014), disponibilidade de instalações, competições e fatores geográficos (McGowin, 2010;Rossing, Nielsen, Elbe & Karbing, 2016), variações climáticas e culturais (Rooney, 1974;Salmela & Moraes, 2003),…”
Section: Introductionunclassified